Situación socioeconómica de las familias de los estudiantes de 9no de EGB en la Unidad Educativa Capitán Edmundo Chiriboga y su impacto en el rendimiento académico de la asignatura de Estudios Sociales - Pilco Fiallos, Cristian Javier (2024)
It is necessary to recognize the importance of socioeconomic factors in education; different social contexts create favorable or unfavorable situations for students at different academic levels; this one, in particular, focused on higher basic education in the subject of Social Studies. When referring to students with a clear family dependency to pursue this academic stage, it is essential to analyze the degree of influence of this social cell as fundamental in providing the necessary economic means. The above is related to the socioeconomic situation of the families of the 9th year EGB students of the Captain Edmundo Chiriboga Educational Unit with different economic possibilities depending on the income they receive, and the amount allocated to education where their influence is considered an essential factor in academic performance in the subject of Social Studies. In this context, the school community must adapt to the existence of various types of families and recognize that these are part of the educational process. Therefore, it is a trilogy where the family component complements the main actors (student and teacher). The new systems of socio-educational relationships must encourage students to reach high motivational and cognitive levels as a condition for comprehensively developing their personalities. Therefore, there is a correlation between the economy and education, directly or indirectly, in basic general education, and the analysis shows that wanting is not enough in a society dependent on the economy, which facilitates the processes of individual and collective improvement.